STRENGTHENING ORGANIZATIONAL COMMITMENT AMONG GENERATION Z EMPLOYEES: AN EMPIRICAL STUDY IN JABODETABEK - Reza Cornelius Soebagio; Joyce A. Turangan (International Journal of Application on Economics and Business, 2026)
Rapid shifts in employment conditions make sustaining employee commitment difficult, particularly for Generation Z, whose distinctive values and high expectations sometimes coincide with perceptions of limited readiness. This paper examines the links between motivation, workload, and workplace conditions and organizational commitment among Gen Z workers in the Jabodetabek area. A questionnaire-based quantitative study of 150 respondents (aged 17–27 with work experience) was estimated using partial least squares structural equation modeling (PLS-SEM). The estimates show that motivation, workload, and the work environment each display positive, statistically meaningful associations with organizational commitment. The evidence offers practical direction for aligning HR practices with Gen Z preferences to strengthen loyalty and curb turnover.